The Geostorm in Great Major Power of the United States and NATO: The Impact of Climate Change to Southeast Asia - Silaen, Christo Ariel Mario; Manurung, Hendra; Pannyiwi, Rahmat (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
This paper aims to describe analytically the geopolitical phenomenon defined as “GEOSTORM” among major powers, specifically focusing on the dynamics between the United States and NATO, and its impact on Southeast Asia landscape through climate change and environmental concerns. As global warming and environmental degradation increase, the interplay between military strategy and ecological sustainability is becoming increasingly important, with the US developing a weather control device that could cause panic worldwide. This research aims to explain how strategic decisions made by these powerful entities not only shape International Relations but also significantly affect the environmental and climate resilience policies of developing countries. Using a multidisciplinary approach, this research integrates theories of international relations, security studies, and global governance to analyze the implications of US and NATO actions on Southeast Asia's ecological landscape. The study examines important issues such as the allocation of military resources, the environmental costs of defense operations, and potential cooperation initiatives aimed at addressing climate change. Southeast Asia regions in the broader context of global governance, and this research highlights the challenges and opportunities that arise from its interactions with major powers. Therefore, by analyzing historical precedents and contemporary developments, the research aims to provide actionable insights for Southeast Asia policymakers in navigating the complexities of big-state politics while fostering a commitment to ecological integrity. Ultimately, this research underscores the need for a comprehensive understanding of how geopolitical maneuvers intersect with environmental interests, advocating for a proactive stance in Southeast Asia foreign policy that aligns with global development of sustainability goals.